2008
DOI: 10.1152/jn.01396.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Sensory Neurons Expressing the Mrgprd Receptor Sense Extracellular ATP and Are Putative Nociceptors

Abstract: Sensory neurons expressing the Mrgprd receptor are known to innervate the outermost living layer of the epidermis, the stratum granulosum. The sensory modality that these neurons signal and the stimulus that they respond to are not established, although immunocytochemical data suggest they could be nonpeptidergic nociceptors. Using patch clamp of dissociated mouse dorsal root ganglion (DRG) neurons, the present study demonstrates that Mrgprdϩ neurons have several properties typical of nociceptors: long-duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 33 publications
4
59
0
Order By: Relevance
“…Previous studies indicated that pharmacological ablation of TRPV1 ϩ afferents causes at least a partial loss of heat pain sensitivity (21)(22)(23). Furthermore, less than 10% of Mrgprd ϩ neurons express TRPV1 in vivo (2,14), and no more than 10% respond to the TRPV1 agonist capsaicin in vitro (17). TRPV1 ϩ and Mrgprd ϩ neurons are therefore largely nonoverlapping populations.…”
Section: Conditional Ablation Of Mrgprdmentioning
confidence: 99%
“…Previous studies indicated that pharmacological ablation of TRPV1 ϩ afferents causes at least a partial loss of heat pain sensitivity (21)(22)(23). Furthermore, less than 10% of Mrgprd ϩ neurons express TRPV1 in vivo (2,14), and no more than 10% respond to the TRPV1 agonist capsaicin in vitro (17). TRPV1 ϩ and Mrgprd ϩ neurons are therefore largely nonoverlapping populations.…”
Section: Conditional Ablation Of Mrgprdmentioning
confidence: 99%
“…RF-amide neuropeptides distinctively activate the mouse MrgA1, MrgA4, MrgC11 and MAS1 receptors (Dong et al 2001;Han et al 2002) and rat MrgC (Grazzini et al 2004). Adenine is an endogenous ligand for MrgA (Bender et al 2002) and -alanine a ligand for MrgD (Shinohara et al 2004), while MrgD is also able to respond to ATP (Dussor et al 2008). Angiotensin metabolites are capable of stimulating MrgD and MrgG (Gembardt et al 2008), while salusin is a surrogate ligand for MrgA1 (Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MRGPRD neurons form synapses in the spinal lamina II (Zylka et al, 2005) and convey their signal monosynaptically to almost all known classes of spinal lamina II neurons, as evidenced by an optogenetical circuit mapping approach . MRGPRD-positive neurons were classified as nonpeptidergic C-fiber nociceptors that coexpress the ionotropic ATP receptor P2X3, tetrodotoxin-insensitive Na V channels, MOP, and partly the TRPV1 ion channel (Shinohara et al, 2004;Zhang et al, 2005;Zylka et al, 2005;Dussor et al, 2008). The functional analysis of these cells for sensory transduction revealed a complex picture.…”
mentioning
confidence: 99%